A single precursor approach for ZIF synthesis: transformation of a new 1D [Zn(Im)(HIm)2(OAc)] structure to 3D Zn(Im)2 frameworks1. Issue 21 (7th June 2015) - Shi, Qi; Wang, Fei; Kang, Xiaozhen; Xu, Jun; Huang, Yining; Li, Jinping; Dong, Jinxiang
<x xml:space="preserve">Abstract</x> We successfully use a 1-dimensional (1D) chain structure with the formula [Zn(Im)(HIm)2(OAc)] (Im = imidazolate, HIm = imidazole, OAc = carboxylate) as a single precursor/source of a metal and ligand to directly prepare 3-dimensional (3D) [Zn(Im)2] frameworks.